Antibody to intermediate filaments of the cytoskeleton. Issue 1 (February 1982) - Osung, O A; Chandra, M; Holborow, E J
Abstract : IgM antibodies against cultures of intermediate filaments (IMF) of the cytoskeleton were demonstrated by immunofluorescence in the sera of 94 (80%) of 118 patients with seropositive rheumatoid arthritis. These antibodies reacted with IMF in cultures of both human fetal fibroblasts and laryngeal carcinoma (HEp2) cells. Of 10 patients from whom paired synovial fluids were also available 8 had anti-IMF antibodies in both serum and fluid. In seronegative RA the incidence of anti-IMF was 40%, in ankylosing spondylitis 25%, in osteoarthrosis 16%, and in normal subjects 14%. Only a minority of RA sera positive for anti-IMF antibodies were also positive for smooth muscle antibody. Absorption experiments suggest that in RA anti-IMF is directed at the intermediate filament protein, vimentin.